LECTURER CORRECTIVE FEEDBACK IN WRITING CLASS ATENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA - NURAINI, ALIF AYU, Mauly Halwat Hikmat, Ph.D, Aryati Prasetyarini, S.Pd, M.Pd (2016)
Alif Ayu Nuraini. A 320 122 003. LECTUREER CORRECTIVE FEEDBACK IN WRITING CLASS AT ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA. Research Paper. Muhammadiyah University of Surakarta. 2016. This study aims to describe the types of corrective feedback used by the lecturers in writing class and to describe the dominant types of corrective feedback used by the lecturers in writing class at the English Department of Muhammadiyah University of Surakarta. The researcher employs descriptive qualitative method. By this method, the researcher uses the lecturer feedback activities in writing class as a data source, and the data of this research are information about the lecturer's corrective feedback given to the students in writing class. The researcher used observation and document in collecting data. Then to analyze the data the researcher used interactive model. The result of this research paper show that first, the researcher found 103 data of lecturers corrective feedback and there are 3 types of lecture corrective feedback and the classification used by the lecturers, namely (1) Oral feedback: 45 data and the classifications are Explicit Correction: 10 data, Recast: 8 data, Clarification Requests: 15 data, Metalinguistic Feedback: 7 data, Elicitation: 3 data, Repetition: 2 data. (2) Positive Feedback (Feedback on content): 47 data and the classifications are Acknowledging a correct answer: 15 data, Indicating an Incorrect Answer: 1 data, Praising: 5 data, Expanding or Modifying Student Answer: 9 data, Repeating: 6 data, Summarizing: 3 data, and Criticizing: 8 data. (3) Negative Feedback (Feedback on form): 11 data and the classifications are Asking the students to repeat: 3 data, Pointing out the error and asking the students to self-correct: 5 data, Commenting on an error and explaining why it is wrong, without having the students repeat the correct form: 2 data, and Asking other students to correct the error: 1 data. Second, the researcher found that, the dominant types of corrective feedback used by the lecturers are Clarification Requests, and Acknowledging a Correct Answer. The researcher found 15 data in each type. Keywords: corrective feedback, writing